Development of Numeracy Literacy Instrument in the Context of Local Wisdom in Pandeglang at the Madrasah Tsanawiyah - Endah - Isnaintri; Hepsi - Nindiasari; Sukirwan - - (Phenomenon : Jurnal Pendidikan MIPA, 2023)
Numeracy literacy, as the ability to understand and apply mathematical concepts in everyday life, has been recognized as a crucial competence in this era. In the context of formal education, many students face challenges in developing their numeracy literacy skills, thus necessitating the development of instruments that have the potential to contribute significantly by being contextual and enriching students' numeracy literacy learning experiences. The aim of this research is to produce a development product of a numeracy literacy instrument based on local wisdom in Pandeglang Regency for grade IX students at Madrasah Tsanawiyah, focusing on number patterns, probability, two-dimensional shapes, and algebraic elements. This research falls under the category of development research, referring to Tessmer's formative research model. The subjects up to the final prototype in this research are 38 students from class IX at MTsN 2 Pandeglang. The instruments used for data collection were validation sheets, interview guidelines, and a numeracy literacy test instrument based on local wisdom in Pandeglang Regency. The data analysis method used involved evaluating the suitability, quality, and accuracy of the developed instrument through expert judgment and statistical analysis. The research results indicate that the developed questions have a good level of validity, although they still require improvement based on the suggestions and feedback provided by the validators. Furthermore, in terms of the quality of the developed test, the difficulty index of the four items falls under the moderate category, the item discrimination is acceptable and valid, and the test exhibits high reliability (0.93). Based on these research results, it can be concluded that the developed numeracy literacy instrument based on local wisdom in Pandeglang Regency is suitable for use.Keywords: Assesment Instrument , Local Wisdom, Mathematics Education, Numeracy LiteracyLiterasi numerasi sebagai kemampuan memahami dan menggunakan konsep matematika dalam kehidupan sehari-hari, telah diakui sebagai salah satu kompetensi penting dalam era ini. Dalam konteks pendidikan formal, banyak siswa menghadapi tantangan dalam mengembangkan kemampuan literasi numerasinya, sehingga diperlukan adanya pengembangan instrumen yang berpotensi memberikan kontribusi penting yang kontekstual dan memperkaya pengalaman belajar literasi numerasi siswa. Tujuan dari penelitian ini adalah untuk menghasilkan produk pengembangan instrumen literasi numerasi berbasis kearifan lokal di Kabupaten Pandeglang bagi siswa kelas IX MTs dengan elemen materi pola bilangan, peluang, bangun ruang sisi datar dan aljabar. Penelitian ini termasuk dalam kategori penelitian pengembangan yang mengacu pada model penelitian formatif Tessmer. Subjek hingga di prototipe akhir pada penelitian ini adalah 38 orang siswa kelas IX di MTsN 2 Pandeglang. Instrumen yang digunakan untuk pengumpulan data adalah lembar validasi, pedoman wawancara dan soal tes instrumen literasi numerasi berbasis kearifan lokal Kabupaten Pandeglang. Metode analisis data yang digunakan adalah dengan mengevaluasi kesesuaian, kualitas dan akurasi instrumen yang dikembangkan melalui ahli dan analisis statistik. Hasil penelitian menunjukkan bahwa bahwa pertanyaan-pertanyaan yang dikembangkan memiliki tingkat validitas yang baik, meskipun masih memerlukan perbaikan berdasarkan saran dan umpan balik yang diberikan oleh validator, selanjutnya untuk kualitas tes yang dikembangkan diantaranya indeks kesukaran keempat soal berada pada kategori sedang, daya pembeda soal dapat diterima dengan baik dan valid serta memiliki realibilitas yang tinggi (0,93). Berdasarkan hasil penelitian tersebut, maka dapat disimpulkan instrumen literasi numerasi berbasis kearifan lokal di Kabupaten Pandeglang yang dikembangkan sudah layak untuk digunakan.